Shapes of Javanese Keris as A Symbolic Sign: Transformation toward The Islamic Period - Ariwibowo, Widodo; Purwasito, Andrik; Pitana, Titis Srimuda (el Harakah: Jurnal Budaya Islam, 2017)
In articulating the visual elements of Keris we will find the concept of symbols, each of which corresponds to the typology of signs. The relationships among the trichotomy signs associated with the codes represent the horizon of the Javanese society regarding the Keris culture. All the Keris signs establish the abstracts relationship model that never has any function before being associated with the code. Principally, people who become the message recipient can perform decoding act by associating the signs with certain conventions. The expression articulation through the Keris elements is a symbol in the typology of signs. The Javanese society’s response or appreciation concerning the invented conventions needs to be investigated to conversely understand the system of signs production. The word kris, as an example, is semiotically classified into other words; keris, dhuhung, dhuwung, curiga, wangkingan, duwung, curiga, and katga, all of which refers to the same sign, which is the tipped stabbing weapons and covered in scabbard. This study found the cultural event of the ideological masking which represents certain period i.e. the deconstructive meanings on the luk of keris (kemba and rengkol) illustrated the ideological transformation from Hinduism to Islamic era. Dalam mengartikulasikan unsur visual Keris kita dihadapkan dengan konsep simbol, di mana setiap simbol sesuai dengan tipologi tanda-tanda. Hubungan antara trikotomi tanda-tanda yang terkait dengan kode mewakili cakrawala masyarakat Jawa tentang budaya Keris. Semua tanda-tanda Keris membangun hubungan abstrak model yang tidak akan pernah memiliki fungsi apapun sebelum dikaitkan dengan kode. Pada prinsipnya orang yang menjadi sasaran penyampaian pesan bisa melakukan decoding dengan cara mengaitkan tanda-tanda pada keris dengan konvensi-konvensi tertentu. Artikulasi ekspresi melalui unsur-unsur dalam Keris memanfaatkan simbol-simbol dalam tipologi tanda. Respons maupun apresiasi orang Jawa terkait dengan konvensi-konvensi yang telah diciptakan para leluhur perlu diketahui untuk melihat secara terbalik dalam sistem produksi tanda. Pemaknaan kata kris misalnya, secara Semiotis dapat diklasifikasikan berdasarkan beberapa kata referensial di antaranya keris, dhuhung, dhuwung, curiga, wangkingan, duwung, curiga, dan katga semua menunjukkan petanda yang sama yaitu senjata tikam yang berhulu dan berwarangka. Penelitian ini menemukan terjadinya peristiwa budaya berupa penopengan (masking) ideologi yang mewakili zaman tertentu, misalnya dekonstruksi pemaknaan bentuk luk keris (kemba dan rengkol) menggambarkan transformasi ideologi zaman Hindhu menuju zaman Islam.